Management and Utilization of Students’ Leftover Food to Reduce Food Waste in the Free Nutritious Meal (MBG) Program: An Islamic Economics Perspective and Integrative Educational Insight - Fitria, Tira Nur (Jurnal Ilmiah Ekonomi Islam, 2025)
This study aims to examine how the management and utilization of students’ leftover food in the Free Nutritious Meal (MBG) Program is viewed through an Islamic economics perspective and its integrative educational value. This study employs a library research design. The analysis shows that the utilization of leftovers from the Free Nutritious Meal (MBG) program reflects core principles of Islamic economics by transforming food surplus into ethically productive resources rather than waste. Practices such as converting leftovers into animal feed, compost, maggot protein, or reprocessed food demonstrate the avoidance of isrāf (wastefulness) and promote moderation (wasatiyyah) in consumption. These efforts ensure that public resources intended for social welfare continue to generate value beyond their primary use. From an Islamic economic perspective, MBG leftover utilization realizes maṣlaḥah (public benefit) by producing multidimensional outcomes, including environmental cleanliness, cost efficiency, educational enrichment, and social welfare. The responsible management of leftovers reflects amanah (trust and accountability), as schools and communities actively assume stewardship over public resources. Collectively, these practices form an emerging Sharia-compliant circular economy, where resources circulate through productive cycles in line with ethical and sustainability principles. Moreover, collaborative management of MBG leftovers strengthens ta‘āwun (cooperation) and social solidarity, while achieving iqtiṣād (balanced efficiency) and ‘adl (justice) without exploitation. By engaging students and communities in ethical consumption and production, these initiatives foster akhlaq iqtisadiyyah, embedding Islamic economic values into everyday behavior. Overall, MBG leftover utilization illustrates how public nutrition programs can operationalize Islamic economic ethics at the grassroots level, addressing food waste, sustainability, and social responsibility in an integrated and practical manner. The utilization of leftovers from the Free Nutritious Meal (MBG) Program serves as an integrative educational practice that simultaneously strengthens student character, promotes environmental sustainability, and enhances economic efficiency. Through hands-on activities such as composting, waste sorting, animal feed production, and food reuse, students internalize ethical values—responsibility (amanah), moderation (wasatiyyah), cooperation (ta‘āwun), and environmental stewardship (khilāfah)—through daily experience rather than abstract instruction. These practices foster creativity, problem-solving, leadership, and integrity in consumption behavior, while positioning schools as experiential and interdisciplinary learning spaces that integrate scientific, economic, civic, and religious perspectives. At both institutional and social levels, MBG leftover management encourages accountability, ethical governance, and community influence, transforming schools into role models of sustainable practice. Overall, MBG leftover utilization elevates the program into a comprehensive educational instrument where character formation, ethical resource management, and sustainable public welfare are deeply interconnected.